Usulan Perbaikan Antrean Truck Pengangkut TBS di Weight Bridge PT Nirmala Agro Lestari dengan Software Promodel - Riri Cornellia (NUCLEUS, 2021)
Queue often causes some problems, one of which is inefficiency in time and expense. PT Nirmala Agro Lestari is endeavoring to optimize the line of TBS truck transports on weight bridge. If the queue at weight bridge PT Nirmala Agro Lestari is going on constantly will result in its slow delivery of TBS to the production area and affect the quality of production. To avoid this, companies conduct queue simulations in order to determine whether the queue system is efficient or should be implemented as an adjustment. PT Nirmala Agro Lestari has always been trying to reach consumer demand targets, with production capacity of 60 tons/hour. The study used the method of queue theory by creating a model of queue simulations based on actual conditions using the promodel. The data on this study is from the TBS transport queue to the weight bridge of PT Nirmala Agro Lestari. The simulation steps on this research was to design an optimum model of line simulation with promodel and test the proposed model for a line model by calculating the workload of TBS trucks. Model modifications are needed because there is still a queue of buildup in the TBS weight bridge loading process. At weight bridge at 90,95%, there is high activity at weight bridge because of the time of service and the frequency of trucks over at the high harvest time that gives trucks a long line of time to enter the production process. The addition of weight bridge to two units shows a utilisation drop on the entry road to the weight bridge from 71.34% to 22.82%, and 90,95% to 62.30%.